Developing a Roadmap for Improving Neglected and Underutilized Crops: A Case Study of South Africa - Mabhaudhi, Tafadzwanashe; Chimonyo, Vimbayi G. P.; Chibarabada, Tendai P.; Modi, Albert T. (Frontiers in Plant Science, 2017)
Reports of neglected and underutilised crops’ (NUS) potential remain mostly anecdotal with limited and often incoherent research available to support them. This has been attributed to lack of clear research goals, limited funding directed at NUS and journal apathy towards publishing work on NUS. The latter points also explain the lack of interest from emerging and established researchers. Additionally, the NUS community’s inability to articulate a roadmap for NUS’ promotion may have unintentionally contributed to this. The current study is a sequel to an initial study that assessed the status of NUS in South Africa. The objective of this follow-up study was then to (i) identify priority NUS, and (ii) articulate a strategy and actionable recommendations for promoting NUS in South Africa. The study identified thirteen priority NUS, categorised into cereals, legumes, root and tuber crops and leafy vegetables based on drought and heat stress tolerance and nutritional value. It is recommended that the available limited resources should be targeted on improving these priority NUS as they offer the best prospects for success. Focus should be on developing value chains for the priority NUS. This should be underpinned by science to provide evidence-based outcomes. This would assist to attract more funding for NUS research, development and innovation in South Africa. It is envisaged that through this roadmap, NUS could be transformed from the peripheries into mainstream agriculture. This study provides a template for developing a roadmap for promoting NUS that could be transposed and replicated among the fourteen other southern African states.